PERSEPSI SISWA TERHADAP PEMBELAJARAN DARING PADA MATA PELAJARAN KONSTRUKSI DAN UTILITAS GEDUNG PASCA COVID-19 - Fiqri, Afdil; Silalahi, Juniman (Jurnal Applied Science in Civil Engineering, 2023)
The Covid-19 pandemic has changed the learning system to distance learning or Online so that learning is implemented online. In the education sector, online learning is an effort to prevent the transmission of Covid-19 and the school at SMKN 2 Panyabungan implements online learning. This study aims to see how students' perceptions of online learning policies during the Covid-19 pandemic. This study aims to see how students' perceptions of online learning and facilitate communication remotely. This research uses quantitative descriptive research. The data collection technique used is in the form of a statement questionnaire with answers Strongly Agree (SS), Agree (S), Strongly Disagree (STS), Disagree (TS) face-to-face to respondents. Respondents in this study were class XI students of SMKN 2 Panyabungan Mandailing Natal Regency, North Sumatra Province. In this study, to analyze the results of questionnaires and student perceptions, descriptive analysis was carried out. The total respondents were 60 students taken by random sampling. The results of this study, using the SPSS application, found a mean of 93.933, median of 92.000, mode of 90.00, std. Deviation of 3.759, minimum of 89.00, maximum of 99.00, sum of 5636.00 so that the Degree of Achievement (DP) of 90.32% is categorized as Very Good. The most common obstacle encountered and experienced is not achieving the connection in the classroom.